Tissue Specific Transcriptome Changes Upon Influenza A Virus Replication in the Duck - Campbell, Lee K.; Fleming-Canepa, Ximena; Webster, Robert G.; Magor, Katharine E. (Frontiers in Immunology, 2021)
Ducks are the natural host and reservoir of influenza A virus (IAV), and as such are permissive to viral replication while being unharmed by most strains. It is not known which mechanisms of viral control are globally regulated during infection, and which are specific to tissues during infection. Here we compare transcript expression from tissues from Pekin ducks infected with a recombinant H5N1 strain A/Vietnam 1203/04 (VN1203) or an H5N2 strain A/British Columbia 500/05 using RNA-sequencing analysis and aligning reads to the NCBI assembly ZJU1.0 of the domestic duck (Anas platyrhynchos) genome. Highly pathogenic VN1203 replicated in lungs and showed systemic dissemination, while BC500, like most low pathogenic strains, replicated in the intestines. VN1203 infection induced robust differential expression of genes all three days post infection, while BC500 induced the greatest number of differentially expressed genes on day 2 post infection. While there were many genes globally upregulated in response to either VN1203 or BC500, tissue specific gene expression differences were observed. Lungs of ducks infected with VN1203 and intestines of birds infected with BC500, tissues important in influenza replication, showed highest upregulation of pattern recognition receptors and interferon stimulated genes early in the response. These tissues also appear to have specific downregulation of inflammatory components, with downregulation of distinct sets of proinflammatory cytokines in lung, and downregulation of key components of leukocyte recruitment and complement pathways in intestine. Our results suggest that global and tissue specific regulation patterns help the duck control viral replication as well as limit some inflammatory responses in tissues involved in replication to avoid damage.